The Development of Inquiry by Using Android-System-Based Chemistry Board Game to Improve Learning Outcome and Critical Thinking Ability - Wardani, S.; Lindawati, L.; Kusuma, S. B. W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
Student’s critical thinking and their learning result depend on learning design and student’s activity. Most students use their spare time with playing game. Students are more challenged by the difficulty in playing game rather than facing the difficulty in understanding the lesson. This phenomenon is the basic reason of the researchers to develop a game that has the essence of the subject matter, namely Chemistry Board Game (CBG) or we can call it with Al Chemist Knight. This research aims to develop a suitable digital game based on android system. In this research media was used to improve the cognitive learning and critical thinking. It also has purpose to evaluate the response of learners in learning chemistry through alkane derived compound topic. The development of this game was adapted from the procedure of game development process in mobile 3D presentation. The collection of evaluation data model applied was pre test and post test in trial class. The result showed that in the pretest the learning result average was 34.35 with classical target of 5%. While the posttest learning result average was 80.51 with classical target of 85%. The n-gain factor was 0.703. Based on the result of the students questionnaire data analysis, 3.025 of students responded positively to the implementation of CBG. A CBG media makes an assessment of critical thinking, in which the indicator of critical thinking which are focusing on questions get 3,1 point, giving arguments get 2.95, asking and answering questions get 3.0, making decision get 3.05, and the average score of critical thinking indicator is 3.025 which belongs to good category. Based on the students’ response questionnaire, we get the average score of 3.3 or 82.5% which is classified in good category.